Modulation of Ryanodine Receptors Activity Alters the Course of Experimental Autoimmune Encephalomyelitis in Mice - Osipchuk, Natalia C.; Soulika, Athena M.; Fomina, Alla F. (Frontiers in Physiology, 2021)
Ryanodine receptors (RyRs), the intracellular Ca2+ release channels, are expressed in T lymphocytes and other types of immune cells. Modulation of RyRs has been shown to affect T cell functions in vitro and immune responses in vivo. The effects of modulation of RyRs on the development of autoimmune diseases have not been investigated. Here we studied how modulation of RyRs through administration of RyR inhibitor dantrolene or introducing a gain-of-function RYR1-p.R163C mutation affects clinical progression of experimental autoimmune encephalomyelitis (EAE) in mice, a T cell-mediated autoimmune neuroinflammatory disease. We found that daily intraperitoneal administration of 5 or 10 mg/kg dantrolene beginning at the time of EAE induction significantly reduced the severity of EAE clinical symptoms and dampened inflammation in the spinal cord. The protective effect of dantrolene on EAE was reversible. Dantrolene administration elicited dose-dependent skeletal muscle weakness: mice that received 10 mg/kg dose developed a waddling gait, while 5 mg/kg dantrolene dose administration produced a reduction in four-limb holding impulse values. Mice bearing the gain-of-function RYR1-p.R163C mutation developed the EAE clinical symptoms faster and more severely than wild-type mice. This study demonstrates that RyRs play a significant role in EAE pathogenesis and suggests that inhibition of RyRs with low doses of dantrolene may have a protective effect against autoimmunity and inflammation in humans.